1995
DOI: 10.1021/j100016a072
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of the Stripe Phase in Lipid Monolayers

Abstract: In lipid monolayers consisting of two phases, the competition between line tension and electrostatic repulsion can give rise to a stripe phase. The stability of this phase with respect to small harmonic distortions is analyzed. It is shown that the stripe phase is just marginally stable when the stripes are of equilibrium width. As soon as the stripes exceed this width, coupled long wavelength distortions are energetically favored.Intermediate results concerning the stability of a single edge and a single stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Our numeric simulations will corroborate this, as rectanglelike domains do indeed dominate in this regime. Finally, it is important to note previous calculations of the stability of isolated stripes [2,15,23], In our terms, they found that the critical width of a stripe, that is, the largest width for which an infinite stripe becomes unstable, is given by dy = eA+y+2, where y is Euler's constant. For an energy-minimized rectangle in the high-aspect-ratio limit, its width is given by tUrec = dy = e A + l, which is strictly less than the critical value for all values of A.…”
Section: F0(a) = 2tc(a + 2 -In 8)mentioning
confidence: 83%
See 3 more Smart Citations
“…Our numeric simulations will corroborate this, as rectanglelike domains do indeed dominate in this regime. Finally, it is important to note previous calculations of the stability of isolated stripes [2,15,23], In our terms, they found that the critical width of a stripe, that is, the largest width for which an infinite stripe becomes unstable, is given by dy = eA+y+2, where y is Euler's constant. For an energy-minimized rectangle in the high-aspect-ratio limit, its width is given by tUrec = dy = e A + l, which is strictly less than the critical value for all values of A.…”
Section: F0(a) = 2tc(a + 2 -In 8)mentioning
confidence: 83%
“…The constant itself can be roughly determined by sampling along the relatively constant region between -2. L ~ Lrec + (c + mn)wTec (15) for A sufficiently negative. This is a remarkably simple charac terization of complicated domain structure, but, as we will see, it indeed holds for domains that resemble the intricate structure of those seen in experiment.…”
Section: Numericsmentioning
confidence: 99%
See 2 more Smart Citations
“…At high temperatures, thermal fluctuations can be described by density fluctuations of colloidal particles, 16,17,30 whereas at low temperatures, thermal fluctuations can be effectively described by shape fluctuations on sharp boundaries separating domains and dispersing medium. 15,[25][26][27][28][29][30][31][32][33] These two descriptions are both widely applied in the literature. In this paper, we focus on the low temperature and density regime where each domain can be treated as an isolated system.…”
Section: Introductionmentioning
confidence: 99%